The fortunate ones a novel - Umansky, Ellen (William Morrow, an imprint of HarperCollinsPublishers, 2017)
One very special work of art--a Chaim Soutine painting--connects the lives and fates of two different women, generations apart, in a novel that moves from World War II Vienna to contemporary Los Angeles.